1952
DOI: 10.1084/jem.96.3.255
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Poliomyelitis and Coxsackie Viruses Following Their Ingestion by Flies

Abstract: Poliomyelitis virus and Coxsackie (or C) virus were quantitatively fed to blowflies, Phormia regina and Phaenicia sericata, and to houseflies, Musca domestica. Naturally infectious human stools were the source of virus. Poliomyelitis virus can be almost quantitatively recovered from flies and from their excreta collected over a period of several days following the feeding. C virus can also be recovered but in lesser yields. No conclusive evidence for virus multiplication in these laboratory-bred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1958
1958
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Later work in the 1950s substantiated this hypothesis by breeding flies (Phormia regina) in the laboratory, infecting them with poliovirus, and determining how much virus they excreted, and for how long (82). While virus could be detected for weeks, no evidence of multiplication was obtained (59). After the coxsackieviruses and the enteroviruses had been recognized, we found that flies collected in the field were often contaminated with these viruses also (56).…”
Section: Introductionmentioning
confidence: 84%
“…Later work in the 1950s substantiated this hypothesis by breeding flies (Phormia regina) in the laboratory, infecting them with poliovirus, and determining how much virus they excreted, and for how long (82). While virus could be detected for weeks, no evidence of multiplication was obtained (59). After the coxsackieviruses and the enteroviruses had been recognized, we found that flies collected in the field were often contaminated with these viruses also (56).…”
Section: Introductionmentioning
confidence: 84%
“…This is particularly well shown in the studies of FENNER et al (1952) with myxomatosis, in which vectors feeding on skin lesions where the concentration of virus is maximum can transmit and those feeding on or through tissues where the concentration is low fail to transmit. This also appears in the studies on rabbit fibroma (KILHAM andDALMAT, 1955}, fowlpox (BRODY, 1936) and poliomyelitis and coxsackie viruses (MELNICK and PENNER, 1952).…”
Section: Mechanical Transmissionmentioning
confidence: 80%
“…However, as indicated in MEYER's (1953) review, external and internal mechanical transmission must be differentiated. The latter mode of transmission is recognized for at least poliomyelitis and coxsackie viruses, on the basis of MELNICK and PENNER's (1952) studies in flies; and possibly for lymphocytic choriomeningitis with bedbugs (MILZER, 1942). The internal mechanical type of vector-virus relationship would also be encompassed by DAY and BENNETTS' (1954) delayedmechanical type of transmission, which is applied to certain vector-borne plant viruses.…”
Section: Inter-relationships Of Viruses and Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabin and Ward (1941) were among the first to appreciate that the alimentary tract was a major site for polio virus replication in man. Studies in the 1940s and 1950s established that although polio virus could be isolated in flies and cockroaches, and antibodies detected in cattle and chimpanzees (Sabin and Ward, 1942, Melnick and Penner, 1952, Sabin and Fieldsteel, 1952, nevertheless the viruses are maintained in nature by human to human transmission. Epidemiological studies in Eskimoes demonstrated that antibodies to polio persisted for at least 40 years in the absence of re-infection and that natural infection gave rise to complete or partial resistance in the intestine.…”
Section: Early History Of Laboratory Studies With Polio Virusmentioning
confidence: 99%